THE INFLUENCE AND EFFICIENCY OF MODEL-DRIVEN MANAGEMENT IN THE HIGHER EDUCATION SYSTEM ON EDUCATIONAL QUALITY (American Journal of Pedagogical and Educational Research, 2025)
At present, the use of convenient and effective methods in the management processes of all sectors has become a pressing issue. From this perspective, optimal management in the pedagogical governance of the higher education system and the improvement of educational quality have become the focus of significant efforts. This article examines the concept of modeling within the interdisciplinary scope of psychology and pedagogy in the context of model-based management of the higher education system and the enhancement of educational quality. Various definitions of models are analyzed, and the main types of models used in current pedagogical research are proposed.